Discourses on Psychological Well-Being and Mental Health of Forced Internally Displaced Persons - Mbatta, Ignasia (Tanzania Journal of Sociology, 2025)
The number of internally displaced persons (IDPs) has risen at an unprecedented rate in recent years, resulting in profound psychological, social, and economic consequences for affected populations. This study provides a comprehensive exploration of the unique challenges and needs experienced by IDPs, synthesising existing literature to offer critical insights for researchers, practitioners, and policymakers striving to improve the mental health and psychosocial well-being of forcibly displaced persons. Employing a qualitative discourse analysis (DA) approach, the study critically examines how psychosocial vulnerabilities among IDPs are constructed, represented, and contested within academic, policy, and humanitarian narratives. It draws upon a range of discourses, including national and international policy documents (e.g., reports from UNHCR, IOM, the Tanzanian government, and humanitarian NGOs), academic literature (peer-reviewed journals and scholarly reports), and public communications (news articles, advocacy texts, and press releases). The analysis centres on key themes such as psychosocial well-being, post-traumatic stress disorder, and the multifaceted challenges and potential opportunities arising from forced displacement. Findings reveal that forced displacement generates both immediate and long-term adverse effects on the mental health and well-being of displaced persons and host communities. Women, children, and other highly vulnerable groups are disproportionately affected by the loss of livelihoods, protective services, social networks, and shelter, factors that intensify psychosocial distress. The study advocates for the integration of mental health and psychosocial support into relocation and displacement planning, emphasising the need to restore dignity, resilience, and hope among displaced populations.